Abortus Provokatus Dalam Perspektif Yuridis - Muyassarotussolichah, Muyassarotussolichah (Musawa Jurnal Studi Gender dan Islam, 2003)
In the Indonesian Code of Criminal Law (KUHP) abortus provocatus criminalis is forbidden and subject to a criminal punishment regardless of the circumstances under which it is conducted. This punishment applies both to the person who undergoes the abortion and also to those persons who assist. This is regulated in passages 346, 347, 348 and 349 of the Criminal Code. Meanwhile in Law No. 23 of 1992, passage 15 in conjunction with passages 80, 81 and 82 which concern health, an exception is made concerning abortion for medical reasons, also known as abortus provocatus medicinalis. The legal sanctions applied to people who have abortions vary from fines to imprisonment. Imprisonment is set out in terms of the maximum, not minimum sentence, so that in practice the court sentence is often very light compared to the legal sanctions listed in the criminal code. In terms of fines, the criminal code itself does not sanction fines for those persons who have abortions, but this matter is further regulated in Law No. 23 of 1992 concerning health, which stipulates a maximal fine of Rp. 500.000.000,- (Five hundred million rupiah).Â